KEBIJAKAN HUKUM PIDANA DALAM PENGGUNAAN RUPIAH DI WILAYAH NEGARA KESATUAN REPUBLIK INDONESIA - Bunga, Dewi (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2016)
The currency is legal tender in Indonesia. The use amount in each transaction in Indonesia will help the stability of the rupiah. In fact, the demand for foreign exchange is very high. The use of foreign currency also used in transactions conducted in Indonesia. Facing these problems, the government issued a regulation to achieve sovereignty of Rupiah. In this study will be discussed on Rupiah usage policy in the territory of the Republic of Indonesia and the policy of the criminal law to ban the refusal to accept the amount. This research is a normative juridical research. Rupiah usage policy in the Homeland must be done as a payment or to settle obligations to be fulfilled by the amount and/ or for other financial transactions in the region except the Homeland as there are doubts over the authenticity of the Rupiah. Criminal law policy to ban the refusal to accept the amount provided for in Article 33 of Law No. 7 of 2011 on Currency that outlines the threat imprisonment and criminal fines. Rupiah usage policy in the Homeland shall be supported by the existence of foreign exchange available, safe and reliable.